Disaster response for small businesses: we must learn from the past. Issue 1 (2nd January 2020) - Gregory, David
ABSTRACT: The frequency and severity of recent natural disasters has raised questions in relation to disaster-related preparedness of the small business sector. Small businesses are an important contributor to local communities and economies. When it comes to recovering from a natural disaster, it is important to support local small businesses to reopen for business as soon as possible. If they are unable to rebound to provide products and services on which we rely as a community, recovery efforts will be curtailed and delayed. This paper provides a practitioner view on the lessons that can be learnt specifically from the Australian experience. The lessons outlined here resonate with small businesses in any disaster recovery context. The insight provided will inform the development of recovery policies and activities in the immediate, short- and long-term at an individual as well as a business level.